IMPLEMENTASI PRAKTIK KERJA LAPANGAN DALAM MENINGKATKAN KOMPETENSI KEAHLIAN SISWA SMK MENGHADAPI TANTANGAN DUNIA KERJA - Karsiyah Wati; Syunu Trihantoyo; Yatim Riyanto (Jurnal Manajemen Pendidikan, 2025)
This research aims to: 1) Determine the implementation of internalization of soft skills, 2) Implementation of the application of hard skills, 3) Improvement and development of hard skills 4). Implementation of entrepreneurial independence. This study uses a qualitative approach. Data collection techniques include interviews and observations, data analysis techniques using qualitative descriptive analysis include data collection, data reduction, data display, and data verification. The results of this study: (1) Internalization of soft skills is carried out systematically through the provision of work culture such as ethics, communication, and adaptation, as well as routine assistance through mentoring, reflection, and independent observation. Monitoring is carried out through journals, supervisor evaluations, and self-assessments, with success measured based on the sustainability of interactions with customers; (2) The application of hard skills is adjusted to the needs of the industry through curriculum synchronization and direct practice using industrial equipment. Learning by doing methods, division rotations, and expertise projects are applied to strengthen students' skills, while quality monitoring is carried out through portfolios and observations by supervisors to ensure that professional standards are met; (3) The development of hard skills is carried out through the provision of tasks with full responsibility during street vendors, external training, and opportunities to become resource persons.